Precise and feasible measurements of lateral calcaneal lengthening osteotomies by radiostereometric analysis in cadaver feet. Issue 5 (May 2015) - Martinkevich, P.; Rahbek, O.; Møller-Madsen, B.; Søballe, K.; Stilling, M.
Abstract : Objectives: Lengthening osteotomies of the calcaneus in children are in general grafted with bone from the iliac crest. Artificial bone grafts have been introduced, however, their structural and clinical durability has not been documented. Radiostereometric analysis (RSA) is a very accurate and precise method for measurements of rigid body movements including the evaluation of joint implant and fracture stability, however, RSA has not previously been used in clinical studies of calcaneal osteotomies. We assessed the precision of RSA as a measurement tool in a lateral calcaneal lengthening osteotomy (LCLO). Methods: LCLO was performed in six fixed adult cadaver feet. Tantalum markers were inserted on each side of the osteotomy and in the cuboideum. Lengthening was done with a plexiglas wedge. A total of 24 radiological double examinations were obtained. Two feet were excluded due to loose and poorly dispersed markers. Precision was assessed as systematic bias and 95% repeatability limits. Results: Systematic bias was generally below 0.10 mm for translations. Precision of migration measurements was below 0.2 mm for translations in the osteotomy. Conclusion: RSA is a precise tool for the evaluation of stability in LCLO. Cite this article: Bone Joint Res 2015;4:78–83.